청소년의 구강건강에 대한 문제 식습관이 구강질환증상 경험에 미치는 영향 - 이은주(Eun-Ju Lee), 이미옥(Mi-Oak Lee) (한국구강보건과학회지, 2020)
Objectives: The purpose of this study is to provide basic data for the improvement of eating habits and development of oral health promotion programs for Korean adolescents by investigating the problems of eating habits and the effects of these causes on the experience of oral disease symptoms by using the online survey on adolescent health behaviors. Methods: A total of 61,858 middle and high school students were identified as the final subjects. Data analysis was conducted with R 3.5.1, and independent t-test and ANOVA were conducted to identify differences in scores on experience of oral disease symptoms according to general characteristics and health behaviors. Multiple regression analysis was conducted to determine the effect of eating habit scores on oral health problems on scores for experience of oral disease symptoms with general characteristics controlled. Results: Oral Health Problems Intake of instant foods, sweets such as sweet drinks, fast foods, and ramen noodles often contain large amounts of sugar, which can be a source of dental caries. In other words, oral health problems such as restricting food can also help oral health. Eating problem control was also a necessary factor for controlling various oral symptoms. As such, eating habits cause various overlapping oral health problems, it is necessary to educate specifically about which oral health foods cause oral health problems. Conclusions: In addition, to protect the oral health of adolescents, foods sold on the market that pose oral health hazards should bear food labels so that adolescents are informed of the oral health risks. KCI Citation Count: 9